Effect of lower-body plyometric training on athletic performance and muscle-tendon properties - Sugisaki, N.; Kurokawa, S. (The Journal of Physical Fitness and Sports Medicine, 2014)
Lower-body plyometric exercises are jumping-type exercises that use an individual`s body weight or a relatively low external load as resistance. In various sports training regimens, lower-body plyometric training is used to improve athletic performance in tasks that require high power generation such as jumping and sprint running. Over the past three decades, numerous studies have investigated the effectiveness of lower-body plyometric training for athletic and neuromuscular performance. The study findings indicated that lower-body plyometric training is effective for improving athletic performance in a wide range of activities. In addition, recent studies have provided knowledge about the adaptation of muscle and tendon components to lower-body plyometric training. These studies showed that neural as well as functional and/or geometrical adaptations occur after plyometric training. However, many issues remain to be fully elucidated. This short review will introduce these recent findings of the effects of lower-body plyometric training on athletic performance and muscle-tendon properties.